Characteristics of Early Phase Clinical Trials for Rare Cancers: Insights From Interviews With Stakeholders - Dooms, M; Saesen, R; Steemans, I; Lansens, J; Huys, I (Frontiers in Pharmacology, 2022)
Background Rare cancers occur with an incidence of no more than 6 cases per 100,000 people It is challenging to perform the necessary clinical studies to investigate safety and efficacy of investigation-al medicines against such malignancies at the earliest stages of drug development. This article investigates the differences between phase I rare cancer trials performed in commercial and non-commercial settings. Materials and Methods The differences were explored through semi-structured interviews with three different target groups: representatives from the academic side (n=7), representatives from the commercial side (n=4) and representatives from patient organizations (n=4). All the interviews were transcribed verbatim and analyzed in NVivo using the framework method. Results According to the interviewees, the academic and commercial sides collaborate in the majority of phase I rare cancer trials. In general, the commercial partner finances the trial, whereas academia is responsible for the execution of the study procedures. The average cost of undertaking these trials depends on what is specifically requested during the trial. The 3+3 study design remains the most widely used design and the use of expansion cohorts is controversial. With regard to the regulatory aspects of phase I rare cancer trials, it was expressed that a good regulatory framework facilitates the conduct of these studies, but that increased regulation and oversight also has drawbacks, e.g. differences in standards between different ethics committees, over interpretation of the rules, insufficient availability of qualified personnel and higher workloads. The patient organization representatives claimed that patients experience no differences in terms of accommodation, compensation and paperwork between the academic and commercial settings and that the degree of follow-up was the same. They also believed that the direct input of patients can bring added value to such studies not only with regard to the recruitment process and the feasibility of the study but also the legibility of the informed consent forms. Conclusion The growing need for first-in-man trials in infrequently occurring malignancies needs to be highlighted, as difficult, not only because rare cancer patients deserve an appropriate treatment, but also because these medicines represent the future of cancer therapy in the precision medicine era.